Tropical Pacific influences on the North Atlantic Thermohaline Circulation - Latif, M. (Annals of Geophysics, 2003)
Most global climate models simulate a weakening of the North Atlantic Thermohaline Circulation (THC) in response to enhanced greenhouse warming. Both surface warming and freshening in high latitudes, the so-called sinking region, contribute to the weakening of the THC. Some models simulate even a complete breakdown of the THC at sufficiently strong forcing. Here results from a state-of-the-art global climate model are presented that does not simulate a weakening of the THC in response to greenhouse warming. Large-scale air-sea interactions in the tropics, similar to those operating during present-day El Niños, lead to anomalously high salinities in the tropical Atlantic. These are advected into the sinking region, thereby increasing the surface density and compensating the effects of the local warming and freshening. The results of the model study are corroborated by the analysis of observations.